ASSESSMENT OF HEMATOLOGIC INDICES AND THEIR CORRELATION TO HEMOGLOBIN A1C AMONG BOSNIAN CHILDREN WITH TYPE 1 DIABETES MELLITUS AND THEIR HEALTHY PEERS - Tihić-Kapidžić, Suzana; Čaušević, Adlija; Fočo-Solak, Jasmina; Malenica, Maja; Tanja, Dujić; Babić, Nermina; Hasanbegović, Sniježana; Begović, Ermin (Journal of Medical Biochemistry, 2020)
Background: Altered level of many hematological parameters have been directly associated with diabetes in adults, while studies on children with type 1 diabetes mellitus are lacking. The aim of this study was to determine hematological indices in diabetic Bosnian children in comparison to healthy controls as well as to correlate their levels to blood glucose and hemoglobin A1c. Methods: 100 healthy and 100 children with type 1 diabetes mellituss (age 1-18 years) were included in this study. Complete Blood Count, Hemoglobin A1c and glucose were tested. Results were analysed by IBM SPSS Statistics version 23.Results: Significant differences (p
Keywords: Hematological indices, Hemoglobin A1c, Type 1 diabetes mellitus, Pediatric population